New data on weevils of the subgenus Pliadonus Reitter, 1912 (Coleoptera: Curculionidae: Otiorhynchus) with the descriptions of three new species from the Caucasus and Turkey - G.E. Davidian (Кавказский энтомологический бюллетень)
Tree new species of the genus Otiorhynchus Germar, 1822 from the subgenus Pliadonus Reitter, 1912 are described from the Caucasus and Turkey: O. karasevi sp. n. from Abkhazia, O. fominykhi sp. n. from Georgia (Mingrelia) and O. neslihanae sp. n. from Georgia (Adjaria) and north-eastern Turkey. Otiorhynchus karasevi sp. n. belongs to the species group of Pliadonus with body covered only by hairs. It is similar to O. dentitibia Reitter, 1888 and O. brachialis Boheman, 1843. Te new species difers from O. dentitibia in the structure of elytra, which are wider and distinctly rounded laterally (in male 1.27–1.48 times as long as wide), distinctly longitudinally convex on disc in basal half. It can be distinguished from O. brachialis in the following features: body is strongly shiny and black, covered by faintly noticeable and rather sparse hairs, penis is subparallel. Otiorhynchus fominykhi sp. n. and O. neslihanae sp. n. belong to the species group of Pliadonus having body covered with hairs and narrow yellowish scales. Otiorhynchus fominykhi sp. n. difers from O. decoratus Stierlin, 1877 in very narrow hair-like scales, which are evenly distributed on the elytra, and in the structure of the aedeagus. It difers from O. reitteri Stierlin, 1876 by evenly distributed scales without spots on elytra. Te body of O. neslihanae sp. n. has distinct evenly distributed narrow lanceolate yellowish scales with faintly noticeable hairs. In contrast to O. karasevi sp. n. and O. fominykhi sp. n., it is characterised by the weakly convex prosternal process, which is faintly defned in lateral view. New data about morphology and distribution of O. reitteri are given. Te lectotypes of O. reitteri and O. frater Stierlin, 1861 are designated. Otiorhynchus frater is transferred from the subgenus Pliadonus to Pocodalemes Reitter, 1912 according to the structure of elytra, fore tibiae and female genitalia